Impact of Fraud in Financial Assistance Programs and Its Prevention: Case Study of Merankabandi, Burundi - Ndayizeye Desire; Kalgi Shah (European Scientific Journal, ESJ, 2026)
The purpose of this study is to examine the frequency and processes of fraud in financial assistance programs, focusing on Merankabandi in Burundi. It aimed to identify systemic vulnerabilities and recommend evidence-based preventive strategies to enhance program integrity and effectiveness. The design, methodology, and approach in this research involve reviewing documents, conducting qualitative analysis, interviewing stakeholders, and observing in the field to thoroughly examine Merankabandi’s governance model in comparison to similar programs worldwide, thereby providing a context for its challenges. The discussions of the findings in this research suggest that there may be either a misunderstanding of fraud or that fraud is genuinely low and unappreciated in Merankabandi, Burundi. The results show structural weaknesses in digital literacy, insufficient aid, and a lack of manual guidance. The implementation of biometric registration and community monitoring organisations has decreased fraud incidents in pilot zones, highlighting the vulnerability of beneficiaries to data collection and targeting processes. This study offers new insights into the interaction between fraud and socioeconomic vulnerability in the aid delivery system. It also introduces a context-specific, field-based approach to prevent and detect fraud, particularly in fragile states.